Transforming Growth Factor Beta 1 Activation, Storage, and Signaling Pathways in Idiopathic Pulmonary Fibrosis in Dogs - Krafft, E. (J Vet Intern Med, 2014)
BACKGROUND: The pathogenesis of idiopathic pulmonary fibrosis (IPF) in dogs is poorly understood. In human, transforming growth factor β1 (TGF‐β1) is considered central in the pathogenesis. OBJECTIVES: To investigate TGF‐β1 pathway in IPF. ANIMALS: Lung tissues from 12 affected and 11 control dogs. Serum from 16 affected West Highland white Terriers (WHWTs) and healthy dogs from predisposed (13 WHWTs, 12 Scottish Terriers and 13 Bichons Frise) and nonpredisposed breeds (10 Whippets, 10 Belgian shepherds, 8 Labradors). METHODS: In this prospective study, immunohistochemistry was used to evaluate expression and localization of TGF‐β1 protein and proteins involved in TGF‐β1 signaling (TGF‐β receptor type I and phospho‐Smad2/3). Pulmonary expression of TGF‐β1 and molecules involved in its storage (latent TGF‐β binding proteins [LTBP] 1, 2, and 4), activation (ανβ6 and ανβ8 integrins, thrombospondin‐1) and signal inhibition (Smad 7) was analyzed by quantitative reverse transcriptase PCR. Circulating TGF‐β1 concentration was measured by ELISA. RESULTS: In IPF, high level of TGF‐β1 protein was found in areas of fibrosis, epithelial cells had strong expression of TGF‐β receptor type 1 and phospho‐Smad2/3, gene expression was decreased for LTBP 4 (P = .009) and β8 integrin (P < .001) and increased for thrombospondin‐1 (P = .016); no difference was seen for Smad7, LTBP1 and 2. Serum TGF‐β1 concentration was higher in predisposed compared with nonpredisposed breeds (P < .0001). CONCLUSIONS AND CLINICAL IMPORTANCE: This study identified an enhanced TGF‐β1 signaling activity in IPF. TGF‐β1 storage and activation proteins with altered expression represent potential therapeutic targets. Higher circulating TGF‐β1 concentration in predisposed breeds might partly explain their susceptibility for IPF.